2007
DOI: 10.1007/s10722-007-9247-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity in a sweet potato (Ipomoea batatas L.) germplasm collection from Tanzania as revealed by AFLP

Abstract: Sweet potato (Ipomoea batatas L.) is the fifth most important crop in the developing countries after rice, wheat, maize and cassava. The amplified fragment length polymorphism (AFLP) method was used to study the genetic diversity and relationships of sweet potato accessions in the germplasm collection AFLP analysis of 97 sweet potato accessions using ten primer combinations gave a total of 202 clear polymorphic bands. Each one of the 97 sweet potato accessions could be distinguished based on these primer combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 29 publications
6
47
2
Order By: Relevance
“…This agrees with a study conducted by Elameen et al (2008) on sweet potato varieties who found that only few of the populations studied had sufficient diversity. Lack of genetic diversity implies that the crop may be susceptible to pest and diseases as there is no enough material to evaluate superior varieties and thus leading to enormous loss of crop.…”
Section: Popsupporting
confidence: 92%
“…This agrees with a study conducted by Elameen et al (2008) on sweet potato varieties who found that only few of the populations studied had sufficient diversity. Lack of genetic diversity implies that the crop may be susceptible to pest and diseases as there is no enough material to evaluate superior varieties and thus leading to enormous loss of crop.…”
Section: Popsupporting
confidence: 92%
“…AFLP analysis [21] was performed as previously described [32], with modifications that included the use of fluorescently labeled primers instead of radioactive labeling. Genomic DNA, (approximately 300 ng) was double-digested using EcoRI and the MseI isoschizomer Tru1I, followed by ligation to the adaptors overnight at room temperature.…”
Section: Aflp Analysismentioning
confidence: 99%
“…China is the highest producer with production figures around 75.6 million tonnes, followed by Tanzania and Nigeria that produce up to 3.57 and 2.73 million tonnes, respectively. Sweet potato is among five most important crops in 40 developing countries beside rice, wheat, maize, and cassava [2].…”
Section: Introductionmentioning
confidence: 99%